Fabrication and characterization of fish-derived collagen scaffold loaded with metronidazole nanoparticle for periodontal bone regeneration - Mohd Zayi, Nora Azirah; Mohamed Halim, Muhammad Lutfi; Harun @ Ismail, Ahmad Fahmi; Mohamad, Mohd Yusof (Universiti Putra Malaysia Press, 2023)
Periodontal disease poses a significant challenge to oral health, affecting the tissue and bone supporting the teeth. Tissue engineering emerges as a promising approach for restoring periodontal tissue and preventing bone loss using scaffolds. However, concern arises when using collagen sourced from mammals like porcine and bovine in scaffolds regarding halal status and disease transmission. Additionally, conventional treatment involves systemic antibiotics to control infection, leading to adverse side effects. This study aims to develop a scaffold using fish-derived collagen incorporated with metronidazole nanoparticles (MNP) and analyze scaffold properties while indirectly addressing safety and halal concerns. The scaffold was fabricated by physically cross-linking collagen derived from the tilapia fish (Tilapia mossambica) and chitosan, with metronidazole nanoparticles (MNP) incorporated into the blend. The scaffold underwent analysis of its physical characteristics, morphology, and pore size using a scanning electron microscope (SEM), swelling, and biodegradability in phosphate buffer solutions (pH 7.4, 37°C). The fish-derived collagen-chitosan exhibited a consistent three-dimensional (3D) physical structure and optimal pore sizes (>100 μm). Scaffolds with MNP concentrations ranging from 0 to 40 w/t% displayed excellent swelling ability and biodegradability, exceeding 80%. As the concentration of MNP increased, the scaffold’s biodegradation rate slowed, suggesting potential as a controlled drug release vehicle aligned with the rates of new bone formation in vivo. In conclusion, the 3D porous scaffold with metronidazole nanoparticles met important criteria for physical structure, pore size, swelling ability, and biodegradability. These halal-compliant scaffolds hold promising potential for applications in tissue engineering and drug delivery and are subject to further in vivo and in vitro studies.